Electromagnetic Characteristics Interpretation of Partial Discharge Phenomena at Variable Distance in High-Voltage Systems - S. M. Kayser Azam; Jun Qiang Chan; Mohamadariff Othman; Wong Jee Keen Raymond; Hazlee Azil Illias; Tarik Abdul Latef; A. K. M. Zakir Hossain; Hamaskutty Vettikalladi; Ali M. Almuhlafi; Mohamed Himdi; Abd Karim Abd Rahman (IEEE Access, 2024)
Insulations at high voltage (HV), whether in HVAC or HVDC systems, often encounter an unwanted partial discharge (PD) phenomenon. PD poses a potential danger to HV insulation and can eventually lead to equipment failures. Out of all electromagnetic (EM) sensing techniques for PD diagnosis, the ultra-high frequency (UHF) method has gained popularity as it allows non-invasive detection at varying distances from PD defects. The EM behavior of PD is significantly affected by the distance between a PD defect and a UHF sensor. This effect varies for different PD defects under different HV conditions. So, considering variable distances, there is a need to analyze EM characteristics of different PD phenomena at different HV conditions. To the best of our knowledge, for the first time, electromagnetic characteristics of different PD defects are experimentally investigated in this work by capturing PD signals from variable distances in both HVAC and HVDC conditions and individually validating their characteristics with EM radiation theories. For wirelessly capturing PD signals, a new UHF sensor is designed with a modified elliptical-shaped antenna on an FR-4 material. The fabricated sensor provides an average realized gain of about 3.66 dBi while covering more than 97% of the total UHF range for PD detection. Applying HVAC, HVDC+, and HVDC–, PDs from three defects (surface, void, free wire) are captured from 1–4 m distances. Interpreted results show that EM radiation in the UHF range from a PD defect is heavily impacted by its detection distance and defect formation despite applied voltage and other conditions being unchanged for the defect. This investigation is particularly beneficial to the variable distance-based PD diagnosis, such as PD localization and handheld PD detection at HVAC/HVDC open substations.